Diabetes mellitus in society: Increasing public awareness through a social approach - Dhika Juliana Sukmana; H. Hardani; Wulan Ratia Ratulangi; A. Aini; Baiq Isti Hijriani; P. Pauzan; Nurul Hadiatun; Denih Agus Setia Permana; Dwi Monika Ningrum (Journal of Community Service and Empowerment, 2023)
Diabetes mellitus (DM) is a non-communicable disease with high morbidity and mortality. Lifestyle and knowledge are crucial factors in the handling and prevention of DM, but public awareness to obtain information is still low. This activity was carried out to increase public awareness in obtaining information and providing education related to DM. Preparation for the activity was carried out from 21 November 2022 and the core activities were in the form of outreach and health checks as a DM screening and were carried out on 24 November 2022. The main target for this activity were residents who had a family history of suffering from DM and risk factors such as obesity and hypertension. From this activity it was found that 90% had high blood pressure and 2 of them had fasting blood sugar levels above 300 mg/dL. In addition, it is known that public awareness to obtain information is still lacking.